Just as I am : a memoir - Tyson, Cicely (HarperCollins Publishers, 2021)
""Just As I Am is my truth. It is me, plain and unvarnished, with the glitter and garland set aside. In these pages, I am indeed Cicely, the actress who has been blessed to grace the stage and screen for six decades. Yet I am also the church girl who once rarely spoke a word. I am the teenager who sought solace in the verses of the old hymn for which this book is named. I am a daughter and mother, a sister, and a friend. I am an observer of human nature and the dreamer of audacious dreams. I am a woman who has hurt as immeasurably as I have loved, a child of God divinely guided by His hand. And here in my ninth decade, I am a woman who, at long last, has something meaningful to say." -Cicely Tyson"--